INHIBITORY ACTIVITY OF MANGIFERIN ON HELICOBACTER PYLORI-INDUCED INFLAMMATION IN HUMAN GASTRIC CARCINOMA AGS CELLS - Zhang, Qiu-jie; Yue, Lu (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Gastric cancer is a serious health issue caused by H. pylori and claims more lives in developing and undeveloped countries. Hence, the need for a natural drug with several pharmacological activities with no adverse effect are highly recommended. The target of this study was to verify the anti-H. pyloric efficacy of mangiferin (MF) on H. pyloriinfected AGS cells. Materials and methods: AGS cells were co-cultured with H. pylori and incubated with increased concentration of MF (10, 20, 50 and 100 μg/mL) or amoxicillin (AMX) and DMSO (control) group to assess its anti-H. pyloric effect by checking inhibitory zone, bacterial drug sensitivity test (MIC and MBC), adhesion and invasive property and various inflammatory markers. Results: Co-culturing of H. pylori-infected AGS cells with MF (100 μg) considerably increased (p<0.05) the inhibitory zone as well as substantially lowered (p<0.05) in the levels of MBC and MIC with decreased adhesion and invasive property in a dose-dependent manner and thus endorsing its anti H. pyloric activity and are almost equivalent to antibiotic AMX. Meanwhile, inflammatory markers such as NF-κB subunit p65, interleukins-1β, IL-8, and TNF-α were also markedly suppressed (p<0.01) on treatment with MF. In addition, the protein expression of inflammatory enzymes like COX-2 and iNOS were notably downregulated (p<0.05) in AGS cells incubated with MF. Conclusion: We, concluded that MF treatment with H. pylori-infected AGS cells significantly suppressed the adhesion and invasion process as well as deactivated NF-p65 thereby blocking inflammatory response and thus lower the incidence of gastric carcinoma.